2008
DOI: 10.1111/j.1744-1617.2008.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Father and Mother Parenting on Children's Mental Health in High‐ and Low‐conflict Divorces

Abstract: This article studied the relations of children's mental health problems to the warmth of their relationship with their noncustodial father and custodial mother and the level of conflict between the parents. Using a sample of 182 divorcing families, multiple regression was used to test the independent effect of father warmth, mother warmth, and interparental conflict. Results indicated that father warmth and mother warmth were both independently related to lower child-externalizing problems. However, the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
78
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 42 publications
13
78
1
9
Order By: Relevance
“…A qualidade da relação da mãe com pai biológico da criança não foi indicada pelos resultados como um preditor dos comportamentos e da competência acadêmica das crianças. Contudo, a qualidade do relacionamento entre os ex-cônjuges pode contribuir tanto com o envolvimento paterno, quanto com o exercício da coparentalidade, o que, por sua vez, refl ete na adaptação da criança à separação conjugal e ao recasamento (Sandler et al, 2008).…”
Section: Tabela 2 Sumário Dos Resultados Dos Conjuntos De Análises Deunclassified
See 1 more Smart Citation
“…A qualidade da relação da mãe com pai biológico da criança não foi indicada pelos resultados como um preditor dos comportamentos e da competência acadêmica das crianças. Contudo, a qualidade do relacionamento entre os ex-cônjuges pode contribuir tanto com o envolvimento paterno, quanto com o exercício da coparentalidade, o que, por sua vez, refl ete na adaptação da criança à separação conjugal e ao recasamento (Sandler et al, 2008).…”
Section: Tabela 2 Sumário Dos Resultados Dos Conjuntos De Análises Deunclassified
“…Segundo Amato, Meyers e Emery (2009), os primeiros estudos sobre a relação da criança com o pai após a separação conjugal enfatizaram a frequência do contato entre pai-fi lho. Contudo, pesquisas mais recentes têm sublinhado a importância da qualidade da relação do pai com a criança para o seu bom desenvolvimento após a separação e o recasamento (Amato, et al, 2009;Sandler, Miles, Cookston, & Braver, 2008). Dessa forma, uma importante tarefa e desafi o que se coloca às novas formas de famílias é manter a coparentalidade após a separação conjugal (Grzybowski, 2011;Troilo & Coleman, 2012).…”
Section: Relação Da Criança Com O Pai Biológicounclassified
“…Studies have shown that 8 to 15 percent of parents continue high conflict, 2-3 years after divorce (Kelly, 2000, Kelly, 2003.There is considerable evidence that most children experience high conflict, verbal and physical violence during their parental divorce (Kelly, 2000;Booth & Amato, 2001;Kelly & Emery, 2003). High conflict between parents following divorce can be traumatic, destroying, and extremely stressful for children and adolescents and it is also the most significant factor for children and adolescents' behavior problems (Amato & Keith, 1991;Emery, 1999;Amato, 2000;Arnett, 2004;Sandler et al, 2008). Emery (1999) in his book "Marriage, divorce, and children's adjustment", noted that parental conflict following parental divorce is significantly related to externalizing behavior problems in children and adolescents.…”
Section: Post-divorce Parental Conflictmentioning
confidence: 99%
“…It has been found that post-divorce parental conflict is more important in influencing the functioning of adolescents than parental divorce. Sandler et al (2008) studied the relationship between children's mental health problems and the level of conflict between the parents by using a sample of 182 divorcing families. Results indicated that father warmth and mother warmth were both independently related to lower child-externalizing behavior problems.…”
Section: Post-divorce Parental Conflictmentioning
confidence: 99%
“…Many studies show that a positive relationship with either the mother or father was associated with fewer mental health problems for children of divorced parents, as compared to not having a close relationship with either parent (Sandler, Miles, Cookston, & Braver, 2008). Unfortunately, after divorce, parents can engage each other in dysfunctional relationships, above all if they didn't accept the end of the marriage.…”
mentioning
confidence: 97%